CRITICAL THINKING SKILLS AND MEANING IN ENGLISH LANGUAGE TEACHING - Harits Masduqi (TEFLIN, 2011)
Many ELT experts believe that the inclusion of critical thinking skills in English classes is necessary to improve studentsâ English competence. Studentsâ critical thinking skills will be optimally increased if meaning is prioritized in English lessons. Those two inter-related elements can be implemented when teachers do collaborative activities stimulating studentsâ thinking process and meaning negotiation. Yet, the realization might be counter-productive if they are applied without careful consideration of task purposes and of studentsâ roles. Based on the consideration, this paper is focused on presenting how critical thinking skills and meaning should be properly incorporated in an English lesson.